How to select favorable and promising alleles and genotypes for breeding: A case study of rice blast resistance genes in Southern and Northeastern China - Xing Wang; Jinyan Wang; Yaling Zhang; Yongxiang Yao; Ying Sun; Liping Lin; Xuemei Ye; Rongbai Li; Zhibin Liang; Yizhen Deng; Qinghua Pan (Crop Journal)
Asian rice comprises two major subspecies: Xian (X) and Geng (G), and the diverged resistance genes (R) have provided a foundation for breeding improved cultivars to control rice blast disease. After conducting two-phase allele mining using six updated FNP marker systems, the functional haplotypes at Pit, Pib, and Pi63 strictly diverged into the X-populations and were defined as X-R loci, while those at Pi54, Pi37, and Pi36 into the G-populations as G-R loci. The genic diversity at the three X-R loci (16 alleles) was twofold higher than that at the three G-R loci (8 alleles), and the allelic diversity in the Southern region (21 alleles) was nearly double that in the Northeastern region (11 alleles). Both observations reflect a significant difference in genetic diversity between X- and G-populations, and indicate that the effective R-genes mainly originated from X-subspecies. Based on the allelic structures characterized by a set of 10 parameters, 8 and 16 alleles were respectively recognized as favorable and promising ones for the regional breeding programs. The genotypic structures of the two regional populations were almost different, indicating that the diverged alleles have been further assembled into two series of regional genotypes through long-term breeding programs, despite the presence of one-third of region-common alleles. The genotypic diversity in the Southern region (55 genotypes) was nearly twice as high as that in the Northeastern region (28), which perfectly reflects the aforementioned differences in both genic and allelic diversities. After analyzing the genotypic structures using a set of 13 parameters, 4 and 23 genotypes, respectively, can be recommended as the favorable and promising ones for the regional breeding programs. The case study serves as a concrete sample of how to identify the favorable and promising alleles and genotypes, and beneficial parents based their comprehensive population structures for gene-designed breeding.